Zachód słońca. Scenariusz filmu kinowego - Filipowicz, Kornel; Różewicz, Stanisław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Zachód słońca. Scenariusz filmu kinowego